Representasi Kekerasan terhadap Perempuan pada Film 27 Steps of May - Lulut Lusianukita; Sunarto . (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Violence against women continues to increase every year, Komnas Perempuan hopes for the ratification of the RUU PKS (Constitutional’s Draft of Eliminating Sexual Violence) to protect victims. But in reality RUU PKS continues to be pros and cons, one of the ways that can be done to voicing minorities is through mass media such as films. Influenced by patriarchal social conditions, it needs to be seen how Indonesian films presenting the theme of violence against women, it is necessary to see how Indonesian films present the theme of violence against women, whether it is told from the point of view of women or men. The study entitled